Calving dynamics at Jakobshavn Isbrae (Sermeq Kujalleq) controlled by local geometry: insights from a 3D Stokes calving model - Iain Wheel; Anna J. Crawford; Douglas I. Benn (Journal of Glaciology)
We present the first simulations of Jakobshavn Isbrae (Sermeq Kujalleq), west Greenland, using a 3D Stokes calving model that permits unrestricted advance and retreat. Using the position-based crevasse-depth calving law, the model is applied to simulate the calving dynamics of 2016–2017 season when Jakobshavn Isbrae is assumed to be stable because of the presence of a strong proglacial ice mélange. The calving law needs to be adjusted to avoid an underestimation of calving, but once adjusted the calving model simulates seasonal calving dynamics that reflect observed calving-driven retreat very well. We find that a crevasse penetration threshold of 94.5% best matches observations from satellite imagery. Additional, 2-year transient simulations show that although ice mélange is essential to the glacier's winter readvance, when removed, the glacier only retreats a couple of kilometres before reaching a stable position. While the backstress provided by the ice mélange allows the glacier to advance beyond this point, the retreated terminus position is determined by a combination of bed geometry and glacier dynamics. Ultimately, while the ice mélange allows winter readvance, cessation of the well-documented rapid retreat of Jakobshavn Isbrae will be influenced by the bed geometry.